ADSORPSI TIMBAL (Pb) DAN ZINK (Zn) DARI LARUTANNYA MENGGUNAKAN ARANG HAYATI (BIOCHARCOAL) KULIT PISANG KEPOK BERDASARKAN VARIASI pH (Adsorption of Plumbum (Pb) and Zinc (Zn) From Its The Solution by Using Biological Charcoal (Biocharcoal) of Kepok Banana) - Darmayanti, Darmayanti; Rahman, Nurdin; Supriadi, Supriadi (Universitas Tadulako, 2012)
The research has been done concerning the adsorption of biological charcoal from kapok banana peel onPb and Zn metal from solution. This study aimed to determine the ability of a banana peel charcoal to adsorbPb and Zn metal from its solution. The method used in this research was a laboratory experiment by using activated charcoal of banana peel as adsorbent ofPb and Zn metal. The absorbed Pb and Zn were measured by using Atomic Absorption Spectrometry (AAS). The results showed that the optimum pH of adsorption of Pb and Zn was obtained at pH 4 and pH 6 respectively with the concentration of Pb and Zn metal was 19.40 mg/g and 21.17 mg/g respectively.